Management of The BAWASLU Oversight Strategy in The Vote Count Stages in The 2020 Concurrent Regional Head Elections for North Halmahera Regency - Renaldo Yacob Garedja; Johny P. Lengkong; Ferry Daud Liando (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Elections are required to be supervised. This is to maintain the sovereignty of the people, the quality of the RHE and to build public confidence in the holding of the RHE. Supervision of RHE implementation is also to maintain the continuity of democratization in Indonesia. Oversight of the RHE implementation process was also institutionalized with the Election Supervisory Body (ESB). In Law 10 of 2016, regarding RHE, it is the Provincial ESB to oversee the Election of the Governor and Deputy Governor and to oversee the election of the Regent and Deputy Regent is the Regency/City Supervisory Committee now changed to ESB in the Regency or City. This study aims to identify and analyze the management of ESB oversight strategies in the vote-counting stages in the 2020 North Halmahera District Election. Simultaneous RHE of North Halmahera Regency in 2020. Researchers focused on the strategic management of ESB supervision in the voting stages of the Simultaneous RHE of North Halmahera Regency using a Strategic Management theory approach according to Fred R. David (2011: 6). The results of this study are the Formulation of the ESB Strategy for North Halmahera Regency to carry out supervision based on ESB Regulations, circular votes and decisions of the Indonesian ESB, as well as supervise according to the schedule and stages in accordance with the applicable General Election Commission Regulations. Monitoring patrols during the quiet period until voting day. Furthermore, carrying out supervision attached to the process of voting and recapitulation of communication votes between ESB organizers and the General Election Commission of North Halmahera Regency is more inclusive so that the supervision process carried out later is not hampered only by the problem of poor communication patterns which are guided by statutory regulations and other derivative regulations, namely ESB Regulations, RI ESB Decrees and pay attention to the 2020 RHE Simultaneous Local Election Circular and Vulnerability Index, surveillance patrols during the calm period until voting day. Furthermore, carrying out supervision attached to the process of voting and recapitulation of votes. Ensuring that equipment for voting and recapitulation of votes is available according to the needs of each polling place.